PENGARUH VARIETAS DAN JENIS PUPUK TERHADAP PERTUMBUHAN DAN HASIL CABAI RAWIT (Capsicum frutescens) - Abdurrohim; Sri Widata; Driska Arnanto (JURNAL ILMIAH AGROUST, 2026)
This research aims to determine the effect of varieties and types of fertilizer on the growth and yield of cayenne pepper. This research was conducted at the Self-Help Agricultural and Rural Training Center (PAS) "Lestari Makmur", Jalan Wates Km. 12 Semampir Hamlet, Argorejo Village, Sedayu District, Bantul Regency, Yogyakarta for approximately 60 days. With an altitude of 88 meters above sea level, the soil type is regosol, with a soil pH of 5.5-7, an average temperature of 26-32oC, and rainfall of 1,654 mm/year. The research was structured in a Complete Randomized Block Design (RAKL), with 2 factorial replications. Factor I is the cayenne pepper variety, namely the original, Bangkok and caliber varieties. Factor II is the type of fertilizer, namely, cow manure, goat manure and NPK fertilizer. Observation variables included plant height, flowering age, number of flowers, number of fruit per plant, length of fruit per hectare, dry weight of the plant, weight of fruit per hectare and fruit weight per hectare. Analysis of the results using variance at a height of 5% to determine the differences between treatments tested with DMRT (Ducan's Multiple Rage Test). The results of the analysis of variance showed that there was no interaction between variety and type of fertilizer on the observed variables of growth and yield of cayenne pepper plants.